Vigorous Physical Activity Is Associated With Better Glycated Hemoglobin and Lower Fear of Hypoglycemia Scores in Youth With Type 1 Diabetes: A 2-Year Follow-Up Study - Jabbour, Georges (Frontiers in Physiology, 2020)
To correlate glycated hemoglobin (HbA1c) and fear of hypoglycemia scores with physical activity (PA) levels in children and adolescents with type 1 diabetes (T1D) over a period of 2 years. Twenty-eight children and 33 adolescents with T1D have been assessed for their PA profile. Personal and medical data for the patients were collected at baseline (visit 0: V0), 1 year later (V1), and 2 years later (V2). At baseline, children with T1D engaged in less moderate to vigorous PA (MVPA) (p < 0.01) per day than adolescents. These results did not differ across visits. On the contrary, adolescents spent fewer time in vigorous physical activity (VPA) (p < 0.01) than children did (p < 0.01). Fear of hypoglycemia scores correlated significantly with VPA levels (β = −0.41, p = 0.03; β = −0.44, p = 0.06; β = −0.61, p = 0.001). For HbA1c (%), significant correlations were reported with VPA levels (β = −0.54, p = 0.02; β = −0.47, p = 0.03; β = −0.62, p = 0.01) across visits. Body mass index percentile correlated with total screen time (β = 0.28, p = 0.02; β = 0.29, p = 0.01; β = 0.31, p = 0.04) and overall PA levels (β = −0.52, p = 0.02; β = −0.42, p = 0.03; β = −0.42, p = 0.01). Performing more vigorous PA a day is associated with better HbA1c with lower perceived fear of hypoglycemia among youth with T1D. Therefore, dedicating more time in VPA may be an appropriate advice for patients with T1D.